Community Based Institutions And Sustainable Livelihoods Of Inland Fishermen Of Bangladesh - Nurul Islam, Gazi Md (2006)

(untitled)
This study investigated the impact of Community Based Fisheries Management (CBFM) on household’s welfare by examining how the various types of assets contribute to household income. A survey of 240 households in Bangladesh was conducted from February to May 2005 to obtain information from fishermen at CBFM and non CBFM sites (control sites). The major objective of CBFM is to build local fishery community organizations for managing fisheries sustainably and improve livelihood conditions of poor fishermen. This is carried out by providing credit, training and developing social awareness so that fishermen’s capacities for managing their livelihood assets are enhanced. A livelihood assets framework is utilized and a regression model is used to analyze the factors that contribute to household income of poor fishermen under the CBFM and in non CBFM control sites.The study finds that the fishermen under CBFM areas have improved their access to different assets such as social capital, human capital, physical capital, financial capital and natural capital. The Principal Component Analysis is used to develop an index of the key variables to be considered in measuring the different asset variables. The results show that the levels of the assets are higher in the CBFM sites compared to the control sites. The participants have acquired use rights of water bodies through administrative support from the government. The organized fishermen participation in making decisions has increased. The participants received higher amount of credit (financial assets) including interest free loans from NGOs to pay for their lease fees and to meet other fisheries related costs. Both the fishermen in the project and control areas have poor productive assets. The fishermen sell their assets during the period of crisis since they do not have savings to fall back to during this period. To examine the relationship between household’s assets and income, the OLS regression is used. The explanatory variables include household characteristics such as age of household head, employment days and household size in addition to livelihood asset variables. The results of the regression show that the social capital, employment days and area of fishing are significant contributors to household income in the project areas. On the other hand, the variables such as household size, age of household head and education are significant factors in determining household income in the control areas. The contribution of social capital factors is significant to household income which indicates that these social factors play a very important role in poverty alleviation in Bangladesh.The overall findings of the study provides support for the development of community based fisheries and the investment in enhancing the multidimensional asset base of rural communities to achieve development goals of poverty alleviation and human development.